Eine Aufgabe der vergleichenden Mandäistik: Die Edition der mandäischen astrologischen Traktate - Băncilă, Ionuţ Daniel (Archaeus, 2016)
The aim of this note is to briefly delineate the task of editing the Mandaean astrological treatises along the lines set by researches nearly 70 years ago as well as according to new scientific insights.